2021
DOI: 10.1111/ppc.12791
|View full text |Cite
|
Sign up to set email alerts
|

Professional quality of life and psychological resilience among psychiatric nurses

Abstract: Purpose: The aim of this study was to determine the relationship between professional quality of life and psychological resilience in psychiatric nurses in Turkey. Design and Methods:A cross-sectional study was conducted with 100 psychiatric nurses in Turkey. Data were collected using the Professional Quality of Life Scale and the Connor-Davidson Resilience Scale.Findings: Correlations were observed between compassion satisfaction (CS) and burnout, CS and resilience, and in burnout and compassion fatigue (CF).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
41
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 42 publications
9
41
3
2
Order By: Relevance
“…The results of the path analysis partially demonstrated the relationships between compassion fatigue, burnout and compassion satisfaction proposed in the hypothesized model. Consistent with the correlation analyses, the statistics of SRW showed that compassion satisfaction exerted a negative moderate effect on burnout, confirming that compassion satisfaction could buffer the negative outcomes of burnout (Sukut et al, 2021; Weintraub et al, 2020). Although a positive and strong correlation between compassion fatigue and burnout has been reported among nurses (Frey et al, 2018; Jarrad & Hammad, 2020), the direct effect of compassion fatigue on burnout has been less explored.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The results of the path analysis partially demonstrated the relationships between compassion fatigue, burnout and compassion satisfaction proposed in the hypothesized model. Consistent with the correlation analyses, the statistics of SRW showed that compassion satisfaction exerted a negative moderate effect on burnout, confirming that compassion satisfaction could buffer the negative outcomes of burnout (Sukut et al, 2021; Weintraub et al, 2020). Although a positive and strong correlation between compassion fatigue and burnout has been reported among nurses (Frey et al, 2018; Jarrad & Hammad, 2020), the direct effect of compassion fatigue on burnout has been less explored.…”
Section: Discussionsupporting
confidence: 74%
“…The results of the path analysis partially demonstrated the relationships between compassion fatigue, burnout and compassion satisfaction proposed in the hypothesized model. Consistent with the correlation analyses, the statistics of SRW showed that compassion satisfaction exerted a negative moderate effect on burnout, TA B L E 2 SRWs and significance of the paths in the final model of path analysis confirming that compassion satisfaction could buffer the negative outcomes of burnout (Sukut et al, 2021;Weintraub et al, 2020).…”
Section: Relationships Between Compassion Fatigue Burnout and Compass...supporting
confidence: 73%
“…Compassion fatigue is strongly correlated with burnout [21,[60][61][62]. Whilst stress and exhaustion are critical attributes of both concepts [21,60] the experience is of being in a 'tired' state in burnout and being in a 'drained' state in compassion fatigue [60] and thus devoid of ones resources [14,60].…”
Section: Compassion Fatigue and Burnoutmentioning
confidence: 99%
“…병원 간호사를 대 상으로 한 최근 연구에 따르면 전문직 삶의 질의 긍정 적 측면을 향상시키기 위하여 회복탄력성을 증진시키기 위한 노력이 필요한 것으로 나타났다 [3]. 간호사의 회복 탄력성이 증진되면 공감만족 수준을 높일 수 있고, 이 를 통하여 소진을 덜 경험하기도 한다 [11]. 나아가 회 복탄력성은 전문직 삶의 질에 매개하여 재직의도에도 긍정적 영향을 미칠 수 있는 것으로 알려져 있다 [3,8].…”
Section: 회복탄력성(Resilience)은 개인적 요인으로서 간호사unclassified
“…먼저 회복탄력성의 경우, 정신과 간호사를 대상으 로 회복탄력성과 공감만족의 유의한 상관관계를 확인한 연구[11]에서 회복탄력성을 증진시킴으로써 공감만족을 높이기 위한 중재가 필요하다고 제언한 것[11]과 연결 된다. 회복탄력성은 전문직 삶의 질에 긍정적 영향을 미치고[3,11], 나아가 이직의도를 낮출 수 있다[1,3,4].국외에서는 혈액종양내과에서 근무하는 간호사를 대상 으로 스트레스가 신체에 미치는 영향을 이해하고 자기 주도적으로 회복탄력성 향상 전략을 수립하는 프로그램 을 적용한 결과, 간호사의 공감만족에 긍정적인 영향을 미치는 것으로 나타났다[26]. 이처럼 간호사가 업무 중 경험하는 스트레스 상황을 극복하고 에너지를 재충전하 기 위한 프로그램은 회복탄력성을 향상시켜 공감만족을 높이는 데 긍정적인 역할을 할 것이다.…”
unclassified